071 Concentric hypertrophic remodelling and subendocardial dysfunction in mitochondrial DNA point mutation carriers. (16th May 2012) - Bates, M G D; Hollingsworth, K G; Newman, J; Jakovljevic, D G; Keavney, B D; Blamire, A M; MacGowan, G A; Chinnery, P F; Turnbull, D M; Taylor, R W; Trenell, M I; Gorman, G S
Abstract : Background: Cardiomyopathy is an independent predictor of morbidity and early mortality in mitochondrial DNA disease, and occurs in 20%–40% of adult patients harbouring the common m.3243A>G mutation, usually with a hypertrophic phenotype. Pathogenetic mechanisms are unclear yet no detailed study of myocardial structure, function and bioenergetics has been performed in m.3243A>G mutation carriers to identify early markers of cardiac involvement. Methods: Cardiac MRI was performed in 20 adult patients (10 males, mean age 38.7±13.1 years) harbouring the m.3243A>G mutation, without clinical evidence of cardiac involvement on routine ECG and echocardiographic screening, and 20 age- and gender-matched healthy controls (10 males, 38.4±14.2 years): (1) phosphorus-31 magnetic resonance spectroscopy, (2) cine imaging (3), cardiac tagging, and (4) late gadolinium enhancement (LGE) imaging on a Philips Intera Achieva 3 Tesla scanner. Clinical disease burden was determined using: (1) the Newcastle Mitochondrial Disease Adult Scale (NMDAS), a 29-domain validated scoring system with a single cardiac domain, and (2) urinary mutation load, the best predictor of overall clinical outcome in m.3243A>G mutation carriers. Results: Compared to control subjects and following Bonferroni correction for multiple comparisons, patients had increased left ventricular mass index (LVMI), LV mass to end-diastolic volume ratio (M/V ratio), LV radial wall thicknesses (all p<0.01), peak torsion and torsion to endocardial circumferential strain ratio (both p<0.05). Longitudinal shortening was decreased in patients (p<0.0001) and correlated with increased LVMI (r=−0.59, p=0.01). These findings are consistent with a reduction in contractile function in the subendocardium compared to the subepicardium, and similar to those reported in familial hypertrophic cardiomyopathy, but there were no differences in diastolic function in our study. Nine patients had diabetes mellitus and 3 had treated hypertension. Among patients, there was no correlation of LVMI or M/V ratio with age, blood pressures, fasting blood glucose or HbA1C but urinary mutation load and NMDAS score correlated strongly with LVMI (r=0.72, p<0.001 and r=0.85, p<0.0001 respectively). Phosphocreatine (PCr)/adenosine triphosphate (ATP) ratio was significantly decreased (p=0.003) in patients (1.57±0.34) compared to controls (1.97±0.22) but there were no associations between PCr/ATP ratio and markers of myocardial function, or mass. No patients displayed evidence of focal myocardial fibrosis on LGE imaging. Conclusions: Concentric remodelling and subendocardial dysfunction are prevalent in m.3243A>G mutation carriers without clinical cardiac disease. Assessment of myocardial deformation may be useful in monitoring disease progression or response to early intervention. Patients with higher urinary mutation loads and disease burden may be at increased risk of cardiac involvement.